2021
DOI: 10.3390/ma14226777
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Simulation of a Radiation Damage Analysis of Biodegradable Polymers

Abstract: In this study, biodegradable poly(L-lactide-co-ε-caprolactone) (PLCL) and poly(L-co-d,l lactide) (PLDLA) were evaluated using Geant4 (G4EmStandardPhysics_option4) for damage simulation, in order to predict the safety of these biodegradable polymers against gamma ray sterilization. In the PLCL damage model, both chain scission and crosslinking reactions appear to occur at a radiation dose in the range 0–200 kGy, but the chain cleavage reaction is expected to be relatively dominant at high irradiation doses abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
3
3
0
Order By: Relevance
“…Furthermore, FTIR spectra were recorded pre-and postirradiation, and no significant difference could be evidenced (data not shown). This agrees with a study by Shim et al 16 who reported that, at gamma-rays doses ranging from 25 to 500 kGy, no significant difference in the polymer chain, and notably the polymer functional groups, before and after irradiation could be seen. In addition, Pérez Davila et al reported a 99.8% similarity in FTIR spectra recorded pre-and postirradiation (25 kGy) of PLA 3D scaffolds.…”
Section: Effect Of the Gamma Irradiation On The Membrane/bg Assemblysupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, FTIR spectra were recorded pre-and postirradiation, and no significant difference could be evidenced (data not shown). This agrees with a study by Shim et al 16 who reported that, at gamma-rays doses ranging from 25 to 500 kGy, no significant difference in the polymer chain, and notably the polymer functional groups, before and after irradiation could be seen. In addition, Pérez Davila et al reported a 99.8% similarity in FTIR spectra recorded pre-and postirradiation (25 kGy) of PLA 3D scaffolds.…”
Section: Effect Of the Gamma Irradiation On The Membrane/bg Assemblysupporting
confidence: 93%
“…However, the Mw of the polymer decreases from ≈350.000 to ≈175.000 g/mol after irradiation, independently of the BG composition. A similar decrease in Mw of polymer was reported by Nugroho et al 42 and Shim et al 16 and can be related to random chain scission. Furthermore, FTIR spectra were recorded pre-and postirradiation, and no significant difference could be evidenced (data not shown).…”
Section: Effect Of the Gamma Irradiation On The Membrane/bg Assemblysupporting
confidence: 86%
See 3 more Smart Citations